2022
DOI: 10.12688/wellcomeopenres.17845.3
|View full text |Cite
|
Sign up to set email alerts
|

A Rational Approach to Drug Repositioning in β-thalassemia: Induction of Fetal Hemoglobin by Established Drugs

Abstract: Drug repositioning and the relevance of orphan drug designation for β-thalassemia is reviewed. Drug repositioning and similar terms ('drug repurposing', 'drug reprofiling', 'drug redirecting', ‘drug rescue’, ‘drug re-tasking’ and/or 'drug rediscovery') have gained great attention, especially in the field or rare diseases (RDs), and represent relevant novel drug development strategies to be considered together with the “off-label” use of pharmaceutical products under clinical trial regimen. The most significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…When our group originally explored the possibility of using rapamycin to treat β-thalassemia [ 89 , 90 , 91 ], knowledge of the action of the drug on erythroid cells was still largely incomplete. On the other hand, many experiments were already designed to characterize agents capable of augmenting HbF levels in humans [ 109 ]. Along this line, our group found that many agents, some of them derived from plants, were indeed able to exert such action in vitro.…”
Section: Ip Protection and Orphan Drug Designationmentioning
confidence: 99%
“…When our group originally explored the possibility of using rapamycin to treat β-thalassemia [ 89 , 90 , 91 ], knowledge of the action of the drug on erythroid cells was still largely incomplete. On the other hand, many experiments were already designed to characterize agents capable of augmenting HbF levels in humans [ 109 ]. Along this line, our group found that many agents, some of them derived from plants, were indeed able to exert such action in vitro.…”
Section: Ip Protection and Orphan Drug Designationmentioning
confidence: 99%
“…In consideration of the role of HbF production in β-thalassemia and SCD, efficient HbF inducers were developed for the treatment of β-thalassemia patients characterized by a low production of HbF [55][56][57][58][59]. Despite the high and growing numbers of HbF inducers, clinical trials are ongoing for a limited number of them, as depicted in Table 1 .…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…6 Examples of chemical drugs have been repurposed for benign prostatic hyperplasia, angina, sedation, nausea, and insomnia; later, they were repurposed for use in hair loss, erectile dysfunction, and leprosy, respectively. 7 Examples of serendipitous discovery include sildenafil, intended Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content.…”
Section: Introductionmentioning
confidence: 99%